Wolność gospodarcza w Polsce po roku 1989 : charakterystyka, przepisy prawa, analiza sondaży - Haromszeki, Łukasz (Economic freedom after the year 1989: characterization, rules of law. Poll's analysis, 2007)
The article presents the meaning of economic freedom in the Polish law. The author uses appropriate publications about this subject. He presents Polish and international regulations of economic freedom. In the second part of article, the author analyzes the Index of Economic Freedom 2007 and several CBOS reports about the meaning of economic freedom in the Polish society in the years 1990-2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 70-79